Impact of Foreshock Transients on the Flank Magnetopause and Magnetosphere and the Ionosphere - Wang, Chih-Ping; Wang, Xueyi; Liu, Terry Z.; Lin, Yu (Frontiers in Astronomy and Space Sciences, 2021)
Mesoscale (on the scales of a few minutes and a few RE) magnetosheath and magnetopause perturbations driven by foreshock transients have been observed in the flank magnetotail. In this paper, we present the 3D global hybrid simulation results to show qualitatively the 3D structure of the flank magnetopause distortion caused by foreshock transients and its impacts on the tail magnetosphere and the ionosphere. Foreshock transient perturbations consist of a low-density core and high-density edge(s), thus, after they propagate into the magnetosheath, they result in magnetosheath pressure perturbations that distort magnetopause. The magnetopause is distorted locally outward (inward) in response to the dip (peak) of the magnetosheath pressure perturbations. As the magnetosheath perturbations propagate tailward, they continue to distort the flank magnetopause. This qualitative explains the transient appearance of the magnetosphere observed in the flank magnetosheath associated with foreshock transients. The 3D structure of the magnetosheath perturbations and the shape of the distorted magnetopause keep evolving as they propagate tailward. The transient distortion of the magnetopause generates compressional magnetic field perturbations within the magnetosphere. The magnetopause distortion also alters currents around the magnetopause, generating field-aligned currents (FACs) flowing in and out of the ionosphere. As the magnetopause distortion propagates tailward, it results in localized enhancements of FACs in the ionosphere that propagate anti-sunward. This qualitatively explains the observed anti-sunward propagation of the ground magnetic field perturbations associated with foreshock transients.